Teori Pembelajaran Humanisme dalam Perspektif Pendidikan Islam - Nurmaida , Desy Khusna; Nasrullah, Nasrullah; Syarifudin, Syarifudin (STAI Auliaurrasyidin Tembilahan, 2022)
Education is a word that is familiar to hear in life. Everyone generally does it. Education does not only take place in school buildings or institutions, but education also exists in the community and family. Previous learning theories have emphasized the role of environmental and cognitive factors in the educational and learning process. The learning process still focuses on the teacher as the main source of knowledge, and schools are the main choice for learning strategies. Humanism theory clearly shows that learning is influenced and guided by the way students think and behave, and by the personal meanings and emotions derived from their learning experiences. This theory seeks to understand learning behavior from the actor's perspective rather than from an observational perspective. This study uses qualitative research with a library research approach. The purpose of this study is to find out how the theory of humanism learning according to the perspective of Islamic education.